รัฐธรรมนูญและสถาบันการเมือง : ศึกษารัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2475 - กัญญา นะรา (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This thesis aims to study political institutions under the Constitution of the Kingdom of Thailand 1932, starting from the process of making the constitution, the political, economic and social context before and during the period when the constitution was in force. This period covers the time between 1932-1964. The study points out that the Constitution of the Kingdom of Thailand 1932 was made by compromise between the monarchy and the People Party. The important principle was the parliamentary system of government having the monarch as the head of state, and the unicameral parliament of all members were elected by the people. However, transitory provisions of the constitution proscribed the parliamentary members had two types, members of the first type came from elections and members of the second type were appointed by monarchy. There was also confirmation of the freedom of the people in writing as well. After the constitution was effective, there was more conflicts between King Rama VII and the member of parliament and the cabinet increasingly. The Monarchy also vetoed several bills and had conflict with the cabinet s policy in several points. Finally, the Monarchy abdicated the throne to cause the Crown to play no role in withholding the abuse of power by other political institutions. The status of the role and relations between the parliamentary members and the government, the real holders of power to appoint second type members were the People Party. Therefore, these members were the group of it and throughout the time this constitution is in force the Prime Minister played a major role in the People Party. For this reason the second type members and the cabinet were in the same group. while the first type members played a role only during the government of Phaya Phaholphonpayuhasena only. Later during Phibulsongkhram s cabinet, the first type members had hardly taken part, because the government used the absolute power in suppression its political enemies. This was caused the balance of power between the legislature and the administration could not have effected in practice. And the cabinet was usually play their role over the members of the parliament. For supporting the right and freedom of the people during the period the constitution took effect, the several law which issued are control to right and freedom. It could be said that the political events took place during the period of this constitution had influence to force the constitution to be unable to fulfill the objective of the parliament system of government. But it could be regarded that this constitution was the beginning of development in the democratic system and paved the way for the parliamentary system of government to emerge in Thailand.